Impact of corporate reputation and personality congruence on consumers' choice of bank. - Chang, Carina Yee Yin. (2010)
This research paper investigates the relationship of two aspects, bank's corporate reputation and the personality congruence between the bank and consumer, on consumer's choice of bank. Three local banks, specifically DBS, OCBC and UOB, are used for the purpose of this study. This paper further delineates the important reputational attributes consumers look for in banks and the dominant corporate characteristics attached to each bank.